Diabetes: glycaemic control in type 2 - Srinivasan, Bala (BMJ Publishing Group, 2008)
INTRODUCTION: Diabetes mellitus is now seen as a progressive disorder of glucose metabolism, affecting about 5% of the population worldwide, over 85% of whom have type 2 diabetes. Type 2 diabetes may occur with obesity, hypertension and dyslipidaemia (the metabolic syndrome), which are powerful predictors of CVD. Blood glucose levels rise progressively over time in people with type 2 diabetes regardless of treatment, causing microvascular and macrovascular complications. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical question: What are the effects of interventions in adults with type 2 diabetes? We searched: Medline, Embase, The Cochrane Library and other important databases up to October 2006 (BMJ Clinical Evidence reviews are updated periodically, please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 69 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: combined oral drug treatment, diet, education, insulin (continuous subcutaneous infusion), insulin, intensive treatment programmes, meglitinides (nateglinide, repaglinide), metformin, monotherapy, blood glucose self-monitoring (different frequencies), and sulphonylureas (newer or older).